2004
DOI: 10.1021/ja0482536
|View full text |Cite
|
Sign up to set email alerts
|

Role of Membrane Potential and Hydrogen Bonding in the Mechanism of Translocation of Guanidinium-Rich Peptides into Cells

Abstract: The results described herein support a mechanistic hypothesis for how guanidine-rich transporters attached to small cargos (MW ca. <3000) can migrate across the lipid membrane of a cell and directly enter the cytosol. Arginine oligomers are found to partition almost completely into the aqueous layer of a water-octanol bilayer. However, when the same partitioning experiment is conducted in the presence of sodium laurate, a representative negatively charged membrane constituent, the arginine oligomer partitions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
549
2
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 563 publications
(587 citation statements)
references
References 18 publications
24
549
2
4
Order By: Relevance
“…98 Other protein-derived or chemically synthesized CPPs such as polyarginines have also been characterized. 99,100 Because of the highly charged nature of CPPs, the same free-energy question for AMPs is also relevant for CPPs. Structural studies of CPPs when bound to lipid membranes thus provide valuable insights into their mechanism of membrane translocation.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…98 Other protein-derived or chemically synthesized CPPs such as polyarginines have also been characterized. 99,100 Because of the highly charged nature of CPPs, the same free-energy question for AMPs is also relevant for CPPs. Structural studies of CPPs when bound to lipid membranes thus provide valuable insights into their mechanism of membrane translocation.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The favorable Coulombic component makes such hydrogen bonds especially strong [19]. Using N-methylated arginine residues, Rothbard and coworkers have elegantly demonstrated that the ability of the guanidinium group to form hydrogen bonds is indeed essential for efficient cellular uptake [20,21].…”
Section: Why Is Polyarginine Internalized By Cells?mentioning
confidence: 99%
“…Many types of transporters have been reported in recent years including peptides (1)(2)(3)(4)(5), peptoids (6), polyamines (7,8), oligocarbamates (9), dendrimers (10,11), polysaccharides (12), steroids (13), cationic lipids (14,15), guanidinoglycosides (16), and even nanotubes (17). These transporters operate through a variety of mechanisms and some through multiple mechanisms depending on cell type, cargo, and other variables (5,(18)(19)(20)(21)(22). Among the classes of transporters, oligoguanidine based transporters are particularly promising, providing excellent water solubility and at the same time the remarkable ability to rapidly cross the nonpolar membrane of a cell.…”
mentioning
confidence: 99%